Factores asociados al síndrome de distres respiratorio en neonatos nacidos en el Hospital Roberto Gilbert de la ciudad de Guayaquil periodo mayo-septiembre- 2019 - Andrango Carchipulla, Wilmer Javier (2019)
Introduction.- In the annual report of the World Health Organization WHO (2012) it is indicated that more than 15 million babies are of preterm birth, and in each year about one million die from complications caused by this type of birth. He also reports that in infant mortality, respiratory distress syndrome is in the first place worldwide. Objectives. - The objective of this academic project is: To determine the factors associated with respiratory distress syndrome in neonates at Roberto Gilbert Hospital in the city of Guayaquil in the period May-September 2019. Methodology: For this, the study was proposed in a sample population of 120 mothers of newborns admitted to the Roberto Gilbert E. hospital in the city of Guayaquil, in the period from May to September 2019, with inductive-deductive method, qualitative-quantitative modality, and descriptive-explanatory-transversal. Results: there was a predominance of the male sex with 79% over the female sex of 41%. This result is related to the data of the gestational age where there was greater incidence in the 29 to 30 weeks of gestation with 75% or 90 neonates Conclusions: The syndrome of respiratory distress is a very recurrent pathology in the newborn and more frequently in very premature and moderate premature infants. During the period of pregnancy, as factors we have recurrent infections in the urinary tract of great presence because it was reported in 91 or 75.83% among the participating mothers, lung maturation as prevention was prescribed in 70.83%.